Self-regulation, stress appraisal, and esport action performance - Trotter, Michael G.; Obine, Emmanuel A. C.; Sharpe, Benjamin T. (Frontiers in Psychology, 2023)
Electronic sport, or esport has seen substantial growth in market value and popularity in the last 10 years. With this growth has come the pursuit elite esports performance, especially in psychology. Continuing this pursuit, this study sought to examine the association between self-regulation and performance in Counter-Strike: Global Offensive (CS:GO) competitors, and subsequently compare these findings with a global sample of e'athletes. The study included a cohort of student competitors (n = 27) and national-level competitors (n = 26). The results unveiled that CS:GO players who displayed higher levels of self-regulation tended to perceive stressful situations as challenges, consequently showcasing superior accuracy and time trial performance. In contrast, individuals with lower self-regulation tended to perceive such situations as threats, which correlated with less favourable performance outcomes. On a broader scale, the study discovered that CS:GO competitors (n = 57) generally exhibited lower levels of self-regulation when compared to the larger population of e'athletes (n = 993). Furthermore, self-regulation was identified as a mediating variable in the relationship between stress appraisal and performance, suggesting that improved self-regulation skills can lead to enhanced accuracy and quicker time trial performance. This implies that competitors with greater self-regulatory abilities perceive themselves as having more personal resources, enabling them to effectively assess challenging situations and employ problem-focused coping strategies. Overall, this research underscores the significance of self-regulation in optimizing esports performance, while providing valuable insights for player development, action performance, and overall outcomes in the field.